ANALISIS KESALAHAN BERBAHASA PADA SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR FAKULTAS ILMU PENDIDIKAN DAN SOSIAL UNIVERSITAS NAHDHLATUL ULAMA BLITAR - Dzakiyatus Sabilla, Ersha; Agus Hermawan; Lailiyatus Sa’diyah; Saptono Hadi (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
Students in the Primary School Teacher Education Program at Nahdlatul Ulama University Blitar's Faculty of Education and Social Sciences in 2022 had their theses reviewed for grammatical and spelling mistakes. This study employs a content analysis strategy based on qualitative descriptive research. Methods for analyzing thesis materials include spotting, categorizing, and rating linguistic errors. Grammar, spelling, word choice, and sentence structure errors were among the many forms of language errors found after painstaking analysis of data extracted from thesis materials. The study's findings show that spelling and grammar mistakes, followed by errors in word choice and sentence structure, are the most common types of language problems. The conclusion of this study highlights the need for enhanced guidance and training in academic writing for students, as well as greater attention from supervising lecturers during the thesis writing process to minimize language errors. This study provides significant contributions to improving the quality of academic writing within the university environment and suggests the implementation of specialized training programs to enhance students' language proficiency in scientific writing.